Sustainable Development Implementation of the Jibril Method in Learning Quran - Melinda, Desi; Elfira, Nini; Sabrina, Rifdah (STIT Ahlussunnah Bukittinggi, 2023)
The minimal variation in Quran learning methods has an impact on students' lack of interest in paying attention to the teacher when giving lessons on how to read the Quran properly and correctly. This research aims to describe the methods used in learning the Quran at the Birrul Walidain Foundation. This research uses qualitative methods, with a descriptive approach. The key informants in this research were teachers at the Birrul Walidain Foundation while supporting informants were students studying at the Birrul Walidain Foundation. Researchers used interviews, documentation, and observation techniques. The collected data was then analyzed using qualitative analysis techniques. The results of this research are that students are taught to memorize, read, write, and meditate on the Quran. Supporting factors for the Quran learning process are manners, parents, and teacher competence. Meanwhile, the inhibiting factors are bad manners and lack of parental control at home. The solution offered is one-on-one dialogue with students and communication between teachers and parents. The results of this research can be applied by other teachers in providing learning about reading the Quran properly and correctly.